GANTI RUGI PENGADAAN TANAH UNTUK KEPENTINGAN UMUM PERSPEKTIF SIYASAH SYAR’IYYAH - Firda, Andi; Kurniati, Kurniati; Budiarti, Budiarti (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The process of procuring land for the public interest often causes problems, especially those related to the amount of compensation that is considered not to pay attention to aspects of justice for landowners. This research aims to find out how the concept of compensation in land procurement and its settlement mechanism from the perspective of siyasah syar'iyyah. The type of research used is literature study research with normative juridical approach and normative theological approach of syar'i. The results of this study show that regulatively, the mechanism of procurement of land for the public interest must be carried out through deliberation between the two parties to determine the amount of indemnity costs. The agreement between the landowner and the government became the basis for the transfer of ownership rights. The mechanism for resolving in case of problems is pursued by deliberation, although litigation efforts are available. In the perspective of siyasah syar'iyyah, the acquisition of land for the public interest can be carried out using the maslahah mursalah method and the government is not justified in acting arbitrarily in taking over ownership of the land but must provide decent and fair compensation.